The Major Determinant Factors Driving Youth Migration in Sri Lanka from 2019 to 2023 - Wickramasinghe, Yasaru (Department of International Studies, Faculty of Social Sciences, University of Kelaniya, Sri Lanka, 2023)
This journal article examines the significant determinant factors that have shaped youth migration trends in Sri Lanka between 2019 and 2023. The study aims to shed light on the multifaceted motivations behind youth migration and their implications for individuals and the broader society. Employing a mixed-methods approach, based on secondary data sources such as e-journals, newspaper articles, news, migration reports, e-articles, websites, e-books, e-data base, and other all kinds of e-sources. To analyze collected data, the method of content analysis is used. The analysis reveals a complex interplay of economic, social, and political factors that have contributed to the rise in youth migration. The economic factors include limited employment opportunities, insufficient wages, and a desire for better livelihood prospects, which have driven young Sri Lankans to seek opportunities abroad. Additionally, the study highlights the role of social factors such as family networks and transnational ties that influence migration decisions. Cultural and educational aspirations also play a part in driving youth to explore new horizons. Moreover, the study delves into the policy landscape and its impact on youth migration. It identifies how policy frameworks addressing education, job creation, and social welfare influence the decisions of young individuals to either migrate or remain in the country. The analysis underscores the need for comprehensive policy measures that address the root causes of youth migration, ensuring that the talents and potential of the country's youth population are effectively harnessed for national development. The findings of this study contribute to a deeper understanding of the dynamics driving youth migration in Sri Lanka during the specified period. The nuanced insights presented in this article serve as a foundation for informed policy discussions and strategies aimed at promoting inclusive development, reducing brain drain, and fostering sustainable opportunities for the country's youth. The research underscores the major driving forces of migration and the importance of taking a holistic approach that acknowledges the intertwined nature of economic, social, and policy factors in shaping migration trends and their implications for the future of Sri Lanka.
Keywords: Determinant Factors, Economy, Migration, Youth